Recycled Plastic–Modified Asphalt Mixtures: Material Behavior, Durability, and Sustainability Implications for Contemporary Road Construction - Dr. Alejandro M. Ríos (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
The increasing accumulation of plastic waste and the escalating demand for durable, cost-effective, and sustainable road infrastructure have jointly intensified scholarly and practical interest in the incorporation of recycled plastics into asphalt mixtures. Over recent decades, asphalt modification has evolved from conventional polymer enhancement toward more environmentally responsive material strategies, among which recycled plastic utilization has emerged as a prominent and contested innovation. This research article presents an extensive, theoretically grounded, and critically elaborated investigation into the use of recycled plastic materials in asphalt mixtures for road construction, drawing strictly upon established literature and standardized testing frameworks. The study synthesizes empirical findings, methodological paradigms, and theoretical interpretations concerning mechanical performance, rheological behavior, moisture susceptibility, aging resistance, and long-term durability of plastic-modified asphalt systems. Particular emphasis is placed on reconciling material science perspectives with pavement engineering requirements and environmental sustainability imperatives. The analysis integrates insights from laboratory-based performance evaluations, binder-level rheological investigations, mixture-level mechanical testing, and aging and moisture damage assessments. It critically examines the influence of plastic type, particle size, incorporation method, and dosage on asphalt behavior across temperature ranges and loading conditions. The study further situates recycled plastic asphalt within the broader discourse on polymer-modified binders, comparing its performance characteristics with crumb rubber, conventional polymers, and hybrid modification strategies. Environmental and socio-technical dimensions are also explored, including lifecycle considerations, waste diversion potential, constructability challenges, and regulatory compatibility. By systematically engaging with the existing body of knowledge, including recent investigations into recycled plastic asphalt mixtures for road construction (Use Of Recycled Plastic In Asphalt Mixtures For Road Construction, 2025), this article identifies persistent knowledge gaps related to long-term field performance, microstructural stability, aging mechanisms, and standardization of design protocols. The findings underscore that while recycled plastic modification can enhance rutting resistance, stiffness, and durability under certain conditions, its performance is highly sensitive to material selection and processing controls. The article concludes by articulating a comprehensive research agenda aimed at advancing recycled plastic asphalt from experimental application toward mainstream, performance-based pavement engineering practice.